2007
DOI: 10.2752/175303707x207945
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of New Primate Exhibits on Zoo Visitors' Attitudes and Perceptions by Using Three Different Assessment Methods

Abstract: Using three different methods, this study investigated how zoo visitors behaved in response to both old and new exhibits of four nonhuman primate species and how they perceived these primates. On-site observations showed that zoo visitors were more likely to stop in front of new exhibits and spend more time viewing new exhibits compared with old exhibits. Response to an on-site questionnaire also showed that zoo visitors perceived primates in the new exhibits more positively than the same animals in the old ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
1
22
0
3
Order By: Relevance
“…Past studies suggest that visitors have more positive perceptions of animals when they are housed in naturalistic exhibits, and tend to prefer naturalistic exhibits over pre-naturalistic exhibits (Finlay, James and Maple 1988;Davey 2006;Nakamichi 2007). Past research has also shown that some forms of stereotypy are directly related to species-typical foraging patterns of that animal (Carlstead, Sidensticker and Baldwin 1991;Wechsler 1991;Lawrence and Terlouw 1993;Fernandez 2010).…”
Section: Visitor Perceptionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Past studies suggest that visitors have more positive perceptions of animals when they are housed in naturalistic exhibits, and tend to prefer naturalistic exhibits over pre-naturalistic exhibits (Finlay, James and Maple 1988;Davey 2006;Nakamichi 2007). Past research has also shown that some forms of stereotypy are directly related to species-typical foraging patterns of that animal (Carlstead, Sidensticker and Baldwin 1991;Wechsler 1991;Lawrence and Terlouw 1993;Fernandez 2010).…”
Section: Visitor Perceptionsmentioning
confidence: 87%
“…Previous studies suggest that visitors spend more time viewing exhibits when an animal is present and active (Bitgood, Patterson and Benefield 1988;Altman 1998;Anderson et al 2003;Davey 2006). There also appears to be a visitor preference for naturalistic exhibits that reflect an animal's wild habitat (Shettel-Neuber 1988;Davey 2006;Nakamichi 2007), and this preference may help create more positive perceptions of zoo animals (Maple 1983;Coe 1985;Finlay, James and Maple 1988;Fernandez et al 2009). …”
mentioning
confidence: 87%
“…Additionally, to a smaller degree, stay times were affected by animal visibility and activity, external factors such as temperature, as well as by visitor characteristics. A similar study examined multiple measures of visitor behavior after four primate species were relocated from small cages to much larger exhibits [Nakamichi, 2007]. Visitors were more likely to pause and had increased stay times at the new exhibits.…”
Section: Zoos and Poementioning
confidence: 99%
“…In this study, we have adopted the tried and tested approach to quantifying visitor behavior, namely using unobtrusive observations of visitors in exhibit settings [see Serrell, 1998 for an extensive description of these techniques]. Although this method was developed in the museum studies field, it has also been widely used in wildlife attractions [Yalowitz and Bronnenkant, 2009; Zwinkels et al, 2009; Moss et al, 2008; Ross and Lukas, 2005; Ross and Gillespie, 2009; Nakamichi, 2007; Bitgood et al, 1988] increasing our confidence in the validity of implementing such an approach. Although, it must be added that the authors recognize other approaches that can be used to assess relative popularity of zoo animals, such as semantic differential scales [Sommer, 2008; Fraser et al, 2006] or conversation analysis [Clayton et al, 2009; Tunnicliffe, 1996], for example.…”
Section: Introductionmentioning
confidence: 99%